Risk Analysis and Mitigation in the Procurement Process of Overhaul Services - Adinda Sushmita Dewanti; Putu Dana Karningsih (IPTEK Journal of Proceedings Series, 2020)
PT. XYZ is one of subsidiaries of state-owned company which has core business in Power Generation and Operation & Maintenance (O&M) Services for power plants. There are a lot of challenges that should be faced by PT. XYZ as a maintenance unit to achieve the on cost, on time and on quality target. Therefore, we need an analysis and risk mitigation in the procurement process of overhaul routine services to assist companies in dealing with potential risks. Risk identification is carried out using literature studies and expert panels. After that, the risk will be analyzed using the Analytic Network Process and House of Risk methods. The use of the ANP method in this study is as additional tools to support the HOR method because in this study it is possible to have a relationship between risk events and risk agents. This relationship is not captured by the HOR method because the HOR method only considers the relationship between the risk event and the risk agent. The results shows that there are 23 risk events that caused by 37 risk agents. Based on ARP result, there are 2 main mitigation efforts that can be done by the company which are increase the coordination between stakeholder and implemented the time-based contract for overhaul routine services. These efforts hopefully could help the company to reduce the probability of risk agents so the overhaul will not be affected.